Micro controller-based system to control the brightness of the lamp - Johari, Noorsasila (2004)
Today, electronics is used in home appliances for multi purposes. This technology increases rapidly because appliances require enhanced features, easy to build and modify while electronics based solutions become cheaper and more sophisticated. Within this evolution, the micro controllers progressively replace analog controllers and discrete solutions even in low cost applications. This paper concerns with the study of micro controller to control the brightness of the lamp. The project consists of two main parts, which are hardware and software. The controller used to perform this project is micro controller PIC16F873. The software was written in PIC language using software development tool, MPLAB. The brightaess of the lamp can be adjusted from minimum level (0% duty cycle) to maximum level (100% duty cycle) using Pulse Width Modulation control technique provided by the micro controller. The brightaess control was examined using multicolour Light Emitting Diode, Direct Current bulb and Alternating Current bulb as an additional.